The role of serum ITF, IBA-1 and Calgranulin B levels in the early diagnosis and prognosis of cervical cancer: Serum ITF, IBA-1 and Calgranulin B levels in cervical cancer - Zhou, Yuxiang; Liu, Jianwei; He, Jiayi; Zhang, Mingying; Zou, Xuehong (Journal of Medical Biochemistry, 2026)
[Objective] To explore the clinical value of serum Intestinal Trefoil Factor (ITF), Ionized Calcium-Binding Adapter Molecule 1 (IBA-1), and Calgranulin B levels in the early auxiliary diagnosis and prognostic evaluation of cervical cancer.[Methods] The cervical cancer group consisted of 256 patients who received a cervical cancer diagnosis at this hospital between January 2023 and June 2024. 150 people who were diagnosed with cervical intraepithelial neoplasia (CIN) at this hospital within the same time period made up the CIN group. 90 women who underwent health checks at this facility throughout the same time period made up the healthy control group. The diagnostic effectiveness of serum ITF, IBA-1, and Calgranulin B levels in patients with cervical cancer, as well as their correlations with clinical indicators and prognosis, were examined, as were changes in these levels in each group.[Results] The cervical cancer group's blood ITF, IBA-1, and Calgranulin B levels were noticeably higher than those of the CIN group and the healthy control group. Compared to the healthy control group, the CIN group's serum ITF, IBA-1, and Calgranulin B levels were considerably higher (P
Keywords: Intestinal Trefoil Factor; Calcium-Binding Adapter Molecule 1; Calgranulin B; Cervical cancer; Prognostic analysis